The Kantian brain: brain dynamics from a neurophenomenological perspective. (April 2015) - Fazelpour, Sina; Thompson, Evan
Highlights: How current views of the brain as a complex, self-organizing system with nonlinear dynamics provide new support for Immanuel Kant's (1724–1804) idea of the 'sponteneity' of cognition. The conceptual and methodological problems raised by the many–many mapping between neural network dynamics and cognitive processes. A neurophenomenological method for addressing these problems that relates the variability of neural network dynamics to the variability of cognitive processes and subjective experience. Abstract : Current research on spontaneous, self-generated brain rhythms and dynamic neural network coordination cast new light on Immanuel Kant's idea of the 'spontaneity' of cognition, that is, the mind's capacity to organize and synthesize sensory stimuli in novel, unprecedented ways. Nevertheless, determining the precise nature of the brain-cognition mapping remains an outstanding challenge. Neurophenomenology, which uses phenomenological information about the variability of subjective experience in order to illuminate the variability of brain dynamics, offers a promising method for addressing this challenge.